(3fXGe GdGKjfjjfs - (3WGdjS, CQSWhs; (3MSjf, Wgs ((3GdbGgQIs (3GdgjFI GdYGeI dbUhQ GdKbGaIs, 2024)
(3eG ef CMmO jToqc aj Cf GdMVGQI GdjhfGfjI TnqcdJ egO GdacQ GdSjGSj, hCfgG GSJWGYJ HeG hYJg ef JLGQH Cf Jchf ednqekI HGdYOjO ef GdfXe GdSjGSjI, hcGf dcd eOjfmI aj GdjhfGf fXGegG GdNGoqU GdPj CQJCJg UGdkMG dgG(B. (3hJYOOJ Jdc GdCfXeI Hjf OjebQGWjI, hedcjI, hCQSJbQGWjI, hCdjLQGcjI, hZjQgG(B. (3hgfG jQUO (S0(3CQSWh(S1 (3GdfXe GdJj JJGHYJ Ydi (S0(3CKjfG(S1 (B((3GdeOjfI GdjhfGfjI GdJj NQL efgG fhQ GdMVGQI(B) (3MJi YGe 403 bHd GdejdGO, ceG jSJYQV COGA eDSSGJ GdOhdI, hTQhW GdMUhd Ydi GdehGWfI(B. (3hJQLY CgejI JQLeI (S0(3Wg MSjf(S1 (3dgPG GdcJGH Edi GdYQHjI Edi chfg hKjbI gGeI ddacQ GdSjGSpqj GdPj cGf SGFkOG aj GdYUhQ GdbOjeI, JDpqcO Ydi Cf GdfXe djSJ LjOkI Ch SjFkI HPGJgG, hdcf JWHjbgG gh eG jLYdgG YGOdkI Ch ZjQ YGOdIs
Keywords: (3QheGs -- (3JGQjNs -- (3GdYUQ GdbOjes